Dielectric bonding for semiconductor-on-insulator applications - Ho, Chiak Ming (2014)
This report investigates the dielectric bonding between two wafers each comprised of a thin film of Aluminium Nitride (AlN) deposited onto a Si substrate as well as the preparations required to ensure the success of the bonding. The two AlN and Si wafers will be brought together under direct contact for bonding to take place, and for successful bonding to occur, the AlN film to be deposited on the surface of the Si wafer must be of high quality, and the AlN-Si wafer must have low contact angle and low RMS surface roughness. Experimental procedures and characterization techniques such as X-ray diffraction, atomic force microscopy, contact angle measurement and O2 surface activation are used to ensure that necessary bonding conditions are met. Direct contact bonding is then performed with two AlN-Si wafers followed by annealing at 300°C for 3 hours to strengthen the bonding between the wafer pair. IR imaging together with the Maszara model is used to examine if the bonding was successful.